2021
DOI: 10.1177/0950422221999222
|View full text |Cite
|
Sign up to set email alerts
|

The Music Den: A framework for entrepreneurship education in a university start-up incubator

Abstract: This account of practice details an ongoing approach to entrepreneurship education currently being implemented at a large urban university in Toronto, Canada. The Music Den is an entrepreneurship incubator focusing on the music industry that collaborates with start-up businesses, music projects, industry, local communities and postsecondary students. The incubator deploys a pedagogical model that promotes self-direction and mentorship by way of adaptable curricular programming. The program design utilizes soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Our study likewise contributes practical insights into ME research. While EE is of interest and benefit to music students, according to previous studies (Hietanen and Ruismäki, 2016;McGee et al, 2021;Schediwy et al, 2018), as far entrepreneurial identity is concerned, there seems to be no significant difference between running EE or not running it in specialised music schools or in schools where pupils engage extensively in ME, including musical instrument practice, improvisation or the like. This interrelationship, however, should not be taken for granted with respect to commercial knowledge and other 'hard' aspects of entrepreneurship if a school aims at developing such competencies among students.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our study likewise contributes practical insights into ME research. While EE is of interest and benefit to music students, according to previous studies (Hietanen and Ruismäki, 2016;McGee et al, 2021;Schediwy et al, 2018), as far entrepreneurial identity is concerned, there seems to be no significant difference between running EE or not running it in specialised music schools or in schools where pupils engage extensively in ME, including musical instrument practice, improvisation or the like. This interrelationship, however, should not be taken for granted with respect to commercial knowledge and other 'hard' aspects of entrepreneurship if a school aims at developing such competencies among students.…”
Section: Discussionmentioning
confidence: 93%
“…Because representatives of creative professions generally lack intellectual property and selling skills (Haukka, 2011; Penaluna and Penaluna, 2009), they may still benefit from EE in this respect, contingent on its delivery (i.e. experiential, hands-on as opposed to merely informative) (McGee et al, 2021). Echoing prior studies, our findings simultaneously hint at treating music classrooms as entrepreneurial identity workplaces in order to support students in reflecting on different aspects of their identity (Harmeling, 2011; Lundqvist et al, 2015) and help resolve known dichotomies between the creative and commercial realms (Schediwy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results showed that the values such as enthusiasm for music and the need for autonomy were not contradictory to the perceived needs of IEE related to professional work. McGee et al (2021) studied the IEE framework of Music Majors. They promoted students’ self-guidance and guidance through adaptive curriculum planning.…”
Section: Methodsmentioning
confidence: 99%
“…If the dialogical nature of knowledge transfer is taken seriously, for instance, third missions’ activities need to identify transfer channels and practices that allow for creating a change within HEIs as well. So far, despite seemingly opening the mission towards a broader understanding of the impact on the broader society, many efforts still focus on collaborations between universities and economic actors and on supporting spin-offs and start-up entrepreneurs (Erikson et al, 2015; Breznitz et al, 2018; Billström, 2020; McGee et al, 2021). Actively engaging with civil society still plays a subordinate role (Berghaeuser and Hoelscher, 2020).…”
Section: Challenging Dialogical Knowledge Transfermentioning
confidence: 99%